In vivo infection models in the pre-clinical pharmacokinetic/pharmacodynamic evaluation of antimicrobial agents. (October 2017) - Andes, David R; Lepak, Alex J
Highlights: The neutropenic murine thigh and lung models are useful antibiotic PK/PD. Infection models are useful for defining the PK/PD index and magnitude. Host and microbe study design features impact the PK/PD target. Murine PK/PD targets correlate with patient outcome. Murine PK/PD target can be used to design clinical trial regimens. Abstract : Animal infection models serve a critical role in the pre-clinical development of antimicrobials. Thoughtful use of these tools can be useful to design and de-risk subsequent clinical trials. Specifically, pharmacokinetic/pharmacodynamic (PK/PD) evaluation of antimicrobials can define the PK/PD driver and target magnitude. In doing so they provide guidance for dosing regimen design and forecast the likelihood of success against target pathogens at the infection site of interest. This review outlines the key design features to consider for successful assessment of experimental output.